The "consumer choice" paradigm in German ordoliberalism and its impact upon EU competition law - Peter Behrens (Europa-Kolleg Hamburg, Institute for European Integration, 2014)
This paper explores the origin and development of the consumer choice paradigm as the core concept of German ordoliberal thought which has had a strong impact on EU competition policy and law. Outside Germany, ordoliberal thought is often identified exclusively with the learning of the original Freiburg School which represents the formative period of German ordoliberalism after the Second World War. Major developments since then have remained largely unrecognized. This paper sets out the important insights that have markedly changed some of the basic concepts of the Freiburg School so as to bring ordoliberalism into line with modern economic learning. The core tenets, however, remain: the crucial role attributed to consumers' choice as the driving force behind producers' rivalry, the dependence of consumers' freedom of choice upon an open market structure, efficiency (consumer welfare) as the result of competition rather than of an individual entrepreneurial market strategy. The core elements of this approach are traced back to classical liberalism and it is shown how they have been enriched and developed beyond the Freiburg School toward the contemporary version of ordoliberalism. This approach is still reflected and should continue to be reflected by the jurisprudence of the ECJ, because it avoids the kind of consumer welfare (or consumer harm) fallacy by which the more economic approach risks to be caught.
Keywords: 320; EU competition law; antitrust law; ordoliberalism; neoliberalism; laisser; faire liberalism; Freiburg School; Chicago School; consumer choice paradigm; consumer welfare paradigm; more economic approach; efficiency; competition as rivalry; competition as a dynamic process of discovery; economic freedom; economic order; economic system; economic planning; centrally directed economy; decentralized exchange economy; social market economy; control of market power; perfect competition; workable competition; system of undistorted competition; public goods; institutional economics; behavioural economics; post-Chicago; economics